Regras fiscais no Brasil e na Europa: Um estudo comparativo e propositivo - Sérgio Wulff Gobetti (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This paper aims to contribute to the debate on possible changes in the Brazilian tax system in the light of recent experience of the European Union (EU) and the United Kingdom, with regard to tax rules. International evidence indicates, according to the International Monetary Fund (IMF) Fiscal Monitor in 2012, we are world facing a new generation of tax rules, more flexible than the prevailing, to meet the surprises of the economic cycle, but also more effective and committed to the sustainability of medium and long-term fiscal policy. In Brazil, however, we still be attached to a fiscal policy model that shows clear signs of wear and obsolescence, in which flexibility has been sought through accounting gimmicks and discretion rather than a new institutional paradigm that increases transparency and credibility. The central proposal of the text is that Brazil walk to adopt fiscal targets based on the concept of structural result adjusted to the economic cycle, such as the EU and the UK.
Keywords: E61; E62; H6; 330; fiscal rules; public deficit; business cycle